A biheteroaryl-bridged fluorescence probe enables lipid droplets-specific bioimaging and photodynamic therapy in clinical clear cell renal cell carcinoma. (April 2021) - Tan, Ping; Li, Chengming; Wang, Yinchan; Zhuang, Weihua; Chen, Mao; Zhou, Linsen; Zhang, Jiapeng; Gong, Qiyong; Wei, Qiang; You, Jingsong
Abstract: Lipid droplets (LDs) targeted fluorescence probe have been believed to be an effective tool for diagnosis and therapy of some tumors with abnormal lipid metabolism, while there are very few probes with simultaneous high efficiency in LDs imaging and inhibiting tumor proliferation. Herein we present a biheteroaryl-bridged fluorescence probe with aggregation-induced emission (AIE) characteristic, which show dual functions of LDs-specific bioimaging and photodynamic therapy (PDT) based on human clear cell renal cell carcinoma (ccRCC) tumor cells and clinical samples, both rich in LDs. The highly LDs-specific targeting capability, good biocompatibility, excellent photostability and imaging resolution of the AIE probe in ccRCC tumor cells make it considerably attractive to commercially available LDs-specific dyes. Notably, the fluorescence imaging in fresh human ccRCC tumor tissues further proves its outstanding LDs-targeting specificity and demonstrates its power as a bio-probe for clinical diagnosis in vitro and in vivo . Confirmatory experiments suggest a superior PDT efficacy of the AIE probe in ccRCC tumor cells in comparison to those LDs-poor tumor cells and normal cells without LDs. Mechanism studies further reveal the presented AIE probe enables to induce the DNA damage and cell apoptosis by reactive oxygen species generation, resulting in desirable therapeutic efficiency for clinical ccRCC tumor cells upon visible light irradiation. Graphical abstract: Image 1